NEEDS ANALYSIS OF MIXED REALITY BASED LEARNING MODEL SAVAR - A. MUHAMMAD SYAFAR; HAMSU ABDUL GANI; MUHAMMAD AGUNG; NURUL FUADI (Pascasarjana Universitas Negeri Makassar, 2024)
The purpose of this study is to analyze the needs for educational media that can enhance students' learning through mixed reality education using industrial control techniques. There are thirty research subjects at Politeknik Bosowa Makassar. This research is an R&D study using the SAVAR (Substitution, Augmentation, Virtual Learning, Apply and Re-evaluation) model. Mixed reality is a technology of unity Augmented reality and virtual reality. The results of this research are an analysis of the execution of the project and a study of the student's characteristics.